Edukacja a „tło migracyjne” – europejskie doświadczenia i dylematy w drodze do integracji - Kapica-Curzytek, Joanna (Kultura-Społeczeństwo-Edukacja, 2018)
Poland is about to face social changes caused by a huge number of refugees and immigrants heading towards Europe. Not all of them come from societies whose culture is close to ours. The crisis of the peaceful idea of coexistence of cultures ((Multikulti) inspires us to analyse the European experience in the process of building integrated society and to draw conclusions. In this way we can avoid repeating some mistakes of other countries. In this situation, education must be a strong foundation of a state policy.